A Framework for Evaluating Economic Impacts of Rooftop PV Systems with or without Energy Storage on Thai Distribution Utilities and Ratepayers - Chaianong, Aksornchan; Bangviwat, A.; Menke, C. (IOP Conference Series: Earth and Environmental Science, 2017)
Driven by decreasing PV and energy storage prices, increasing electricity costs and policy supports from Thai government (self-consumption era), rooftop PV and energy storage systems are going to be deployed in the country rapidly that may disrupt existing business models structure of Thai distribution utilities due to revenue erosion and lost earnings opportunities. The retail rates that directly affect ratepayers (non-solar customers) are expected to increase. This paper focuses on a framework for evaluating impacts of PV with and without energy storage systems on Thai distribution utilities and ratepayers by using cost-benefit analysis (CBA). Prior to calculation of cost/benefit components, changes in energy sales need to be addressed. Government policies for the support of PV generation will also help in accelerating the rooftop PV installation. Benefit components include avoided costs due to transmission losses and deferring distribution capacity with appropriate PV penetration level, while cost components consist of losses in revenue, program costs, integration costs and unrecovered fixed costs. It is necessary for Thailand to compare total costs and total benefits of rooftop PV and energy storage systems in order to adopt policy supports and mitigation approaches, such as business model innovation and regulatory reform, effectively.
Created from Fastlane, Scopus look-up

An analysis for promoting residential-scale solar photovoltaic (PV) in Bangkok, Thailand - Chaianong, Aksornchan (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)

Bill saving analysis of rooftop PV customers and policy implications for Thailand - Chaianong, Aksornchan; Tongsopit, Sopitsuda; Bangviwat, Athikom; Menke, Christoph (Renewable Energy, 2019)
Since a new policy supporting rooftop photovoltaics (PV) will be launched in Thailand, this study investigates the economics of utility customers’ investments in rooftop PV (values of bill savings) for four customer groups (residential scale, small general service, medium general service and large general service) across electricity tariffs, PV-to-load ratios and compensation schemes (net metering and net billing). The values of the bill savings of all groups are higher under the conditions of higher buyback rates/credit, lower PV-to-load ratios, and higher retail rates. Under the current retail rate design, the values of the bill savings of residential and small general service groups are slightly higher than those of medium and large general service groups, since there are demand charges for the latter two groups that cannot be completely avoided using rooftop PV. Load shapes do not significantly impact the values of the bill savings for all customer groups. Additionally, net metering causes a smaller variation in bill savings as compared to net billing, implying more flexibility for the customers to size their PV systems over a broader range. In contrast, net billing would encourage customers to limit their PV sizes, thereby mitigating the concerns of the utilities.
Created from Fastlane, Scopus look-up
Keywords: Bill savings; Net billing; Net metering; Rooftop PV; Thailand

Cost–benefit analysis of rooftop PV systems on utilities and ratepayers in Thailand - Chaianong, Aksornchan; Bangviwat, Athikom; Menke, Christoph; Darghouth, Naïm R. (Energies, 2019)
Driven by falling photovoltaic (PV) installation costs and potential support policies, rooftop PV is expected to expand rapidly in Thailand. As a result, the relevant stakeholders, especially utilities, have concerns about the net economic impacts of high PV adoption. Using a cost–benefit analysis, this study quantifies the net economic impacts of rooftop PV systems on three utilities and on ratepayers in Thailand by applying nine different PV adoption scenarios with various buyback rates and annual percentages of PV cost reduction. Under Thailand’s current electricity tariff structure, Thai utilities are well-protected and able to pass all costs due to PV onto the ratepayers in terms of changes in retail rates. We find that when PV adoption is low, the net economic impacts on both the utilities and retail rates are small and the impacts on each utility depend on its specific characteristics. On the other hand, when PV adoption ranges from 9–14% in energy basis, five-year retail rate impacts become noticeable and are between 6% and 11% as compared to the projected retail rates in 2036 depending on the PV adoption level. Thus, it is necessary for Thailand to make tradeoffs among the stakeholders and maximize the benefits of rooftop PV adoption.
Created from Fastlane, Scopus look-up
Keywords: Cost–benefit analysis; Ratepayer; Rooftop PV; Thailand; Utility

Customer economics of residential PV–battery systems in Thailand - Chaianong, Aksornchan; Bangviwat, Athikom; Menke, Christoph; Breitschopf, Barbara; Eichhammer, Wolfgang (Renewable Energy, 2020)
The currently high upfront costs of batteries and the low retail electricity prices of households make investments in PV–battery systems not yet economically feasible. However, the experiences/learning curves of renewable generation technologies lead to the assumption that battery prices will rapidly decline with increasing diffusion. Furthermore, projected retail electricity rates are expected to increase with rising electricity demand. This study investigates the returns to residential customers using PV–battery systems under decreasing battery prices in Thailand. The impacts of four additional parameters have been included. The analysis is based mainly on net present values (NPV) and levelized costs of electricity (LCOE). The results show that battery size and its cost, and retail rate design have significant impacts on the returns, whereas buyback incentives for excess electricity have the lowest impact. In addition, to increase the power system flexibility by using PV–battery systems, the Thai government should provide the appropriate financial support, by which the savings incurred by the grid extension investments compensate for the costs.
Created from Fastlane, Scopus look-up
Keywords: Battery; Customer economics; PV; Residential; Rooftop; Thailand

Datasets and time series for energy policy research and modelling - Chaianong, Aksornchan; Hoffart, Franziska M.; Kerker, Nina; Lilliestam, Johan; Weko, Silvia (1. NFDI4Energy Conference 2024, 2024)
To reach the Paris Agreement’s goal to limit global warming to 1.5°C, a crucial system-wide transformation, and relevant public policies are required to push toward a sustainable, innova- tive, and inclusive future for different sectors, including the energy sector [1]. Interdisciplinary energy models have become essential tools to support the policy-making process of the low- carbon transition, as discussed in [2], [3]. However, most empirical analyses rarely focus on integrating social and political factors into their studies. Moreover, published open-access en- ergy policy research datasets are scarce or not in machine-readable formats [4]. As a result, we aim to develop practices for collecting datasets for energy policy-related research that could support more efficient research in the field and enable the quantitative analysis of energy pol- icy/social and political factors into energy modelli

Forecast of rooftop PV penetration in Bangkok, Thailand - Chaianong, Aksornchan; Bangviwat, Athikom; Menke, Christoph; et al. (41st IAEE International Conference, 2018)

How to design an area-based prioritization of biogas production from organic municipal solid waste? Evidence from Thailand - Chaianong, Aksornchan; Pharino, Chanathip (Waste Management, 2022)
To properly manage municipal solid waste (MSW) and meet the country's biogas target, it is necessary for the government to prioritize their support to areas/provinces that have high resource potential. Therefore, this work designed a holistic approach for nationwide area-based organic MSW to biogas potential estimation. The total biogas power potential was ranged from 999 MW in 2021 to 1,652 MW in 2037. Moreover, priority setting on area-based biogas implementation was proposed, based on its resource potential to efficiently promote such technology. To achieve current biogas target of the country, the study identified 28% of national area coverage as priorities for actual execution, which could offset averagely 3% per year. To support design and planning purposes, an area with around 45,000 capita is recommended for developing 1 MW of MSW to biogas power plant using anaerobic digestion technology. The methodology development from this research revealed the link between resource potential and area-based prioritization framework that could be adopted in any growing economies to couple waste management with renewable energy production.
Created from Fastlane, Scopus look-up
Keywords: Anaerobic digestion; Area-based biogas; Organic MSW; Prioritization; Thailand; Waste-to-energy

Impacts of traffic data on short-term residential load forecasting before and during the COVID-19 pandemic - Chaianong, Aksornchan; Winzer, Christian; Gellrich, Mario (Energy Strategy Reviews, 2022)
Accurate load forecasting is essential for power-sector planning and management. This applies during normal situations as well as phase changes such as the Coronavirus (COVID-19) pandemic due to variations in electricity consumption that made it difficult for system operators to forecast load accurately. So far, few studies have used traffic data to improve load prediction accuracy. This paper aims to investigate the influence of traffic data in combination with other commonly used features (historical load, weather, and time) – to better predict short-term residential electricity consumption. Based on data from two selected distribution grid areas in Switzerland and random forest as a forecasting technique, the findings suggest that the impact of traffic data on load forecasts is much smaller than the impact of time variables. However, traffic data could improve load forecasting where information on historical load is not available. Another benefit of using traffic data is that it might explain the phenomenon of interest better than historical electricity demand. Some of our findings vary greatly between the two datasets, indicating the importance of studies based on larger numbers of datasets, features, and forecasting approaches.
Created from Fastlane, Scopus look-up
Keywords: COVID-19; Load forecasting; Machine learning; Random forest; Traffic

Integration of regulatory constraints from a policy database into the energy system modeling tool atlite - Davidson, Hannah; Chaianong, Aksornchan; Qussous, Ramiz; Milioritsas, Ioannis; Lilliestam, Johan; Schäfer, Mirko (NFDI4Energy, 2025)
Energy system optimization models are widely used tools to design and analyze cost- efficient system transformation pathways, identify trade-offs and no-regret solutions, or to investigate the influence of different assumptions and boundary conditions on sys- tem characteristics [1]. Such models integrate a broad range of parameters, including technological costs, resource availability, emissions limits, but also implicit representa- tions of socio-political factors like land-use restrictions or limits to the diffusion of new technologies. Data for technical parameters or cost estimates generally are available from differ- ent sources in well-structured form, allowing direct and explicit model integration and transparent discussion of input data setting for energy system optimization models. In contrast, the inclusion of societal or political factors often is more implicitly entangled in the modeling process, for instance through boundary conditions or the choice of spe- cific demand patterns [2]–[5]. Modeling studies with a focus on the influence of such factors thus often cannot draw on already existing data sets, but rather collect and integrate specific data for a specific modeling purpose [6
Keywords: energy system modeling; policy database; wind power capacity expansion

NDC Transparency Meta-study - Chaianong, Aksornchan; Castro, Paula (2023)

Outlook and challenges for promoting solar photovoltaic rooftops in Thailand - Chaianong, Aksornchan; Pharino, Chanathip (Renewable & Sustainable Energy Reviews, 2015)
Solar photovoltaic (PV) rooftops have significant potentials for reducing reliance on conventional energy source and enhancing energy security in response to emergency situations or in remote areas. Widespread adaptation of solar PV rooftops can also help address climate change issue via lower overall emission of Greenhouse Gases. This paper reviewed the latest situation of solar PV rooftop implementation, expansion and execution strategies in Thailand. The review examined factors impacting adoption rate of solar PV rooftops. Supporting factors include optimum solar radiation intensity, active renewable energy development policy and Feed-In Tariff (FIT). Increasing urbanization rate also resulted in an increase in potential space suitable for solar panel installation. Barriers of solar PV rooftop implementation in Thailand were carefully analyzed. Limitation in domestic technology and technical experiences in manufacturing sector is one of the major barriers inhibiting progress in solar rooftop adoption. In addition, government subsidy and support are still needed for solar PV rooftops to be competitive with other forms of energy generation. Increasing public awareness and reforming of energy and related regulations are necessary to promote meaningful implementation of solar energy in Thailand. To enhance rate of solar PV rooftop installation in Thailand, a short-term strategy could be in a form of providing financial supports such as low interest rate loans, tax credits and development of renewable portfolio standards together with the current FIT scheme. In the longer-term, to achieve grid parity, the government and private sectors need to rely less on financial subsidies and focus on establishing R&D centers to develop and strengthen domestic solar energy industry and introduce cost-effective solar PV solutions. With effective policies and credible solutions with a viable market, public demand in solar rooftop implementation in urban areas will naturally increase and create sustainable progress in solar rooftop industry in Thailand.
Created from Fastlane, Scopus look-up
Keywords: Energy security; Low carbon electricity; Renewable energy; Solar PV policy; Solar rooftop energy; Thailand

Pathways for enhancing sustainable mobility in emerging markets: Cost-benefit analysis and policy recommendations for recycling of electric-vehicle batteries in Thailand - Chaianong, Aksornchan; Pharino, Chanathip; Langkau, Sabine; Limthongkul, Pimpa; Kunanusont, Nattanai (Sustainable Production and Consumption, 2024)
To transition towards sustainable mobility in emerging economies, fostering the use of electric vehicles (EVs) is required. This necessitates the development of an efficient management system for end-of-life (EoL) EV batteries under a circular economy principle. Using Thailand as a case study, this paper provides a holistic analysis by developing a Cost-Benefit Analysis (CBA) and deriving policy implications from the CBA results that consider stakeholder perspectives at the micro level and the uncertainties of future development. The findings suggest that the economies of scale (plant centralization) and the share of cathode chemistries play pivotal roles. In some cases, investment incentives may be required depending on the inflow of EoL batteries, technological advancements, and market volatility. A policy mix combining EoL volume-focused (i.e., enhancing battery collection rates/imports and establishing a clear policy roadmap for scaling up recycling operations) and monetary measures (i.e., taxes and financial subsidies) is essential to establish recycling facilities.
Created from Fastlane, Scopus look-up
Keywords: Circular economy; Cost-Benefit Analysis; Electric vehicle; Lithium-ion battery; Recycling; Sustainable mobility

Process integration of dimethyl carbonate and ethylene glycol production from biomass and heat exchanger network design - Choomwattana, Chayanit; Chaianong, Aksornchan; Kiatkittipong, Worapon; Kongpanna, Pichayapan; Quitain, Armando T.; Assabumrungrat, Suttichai (Chemical Engineering and Processing, 2016)
This work proposed an integrated production process of dimethyl carbonate (DMC) and ethylene glycol (EG) from biomass. The process started with biomass gasification, CO2 separation and CO2 conversion to ethylene carbonate. DMC and EG were produced via transesterification using reactive distillation and extractive distillation. Various key parameters were examined to optimize operating condition focusing on heat consumption. DMC and EG can achieve 99.5 mol% purity. The process can sustain itself without any external heat sources by using biomass combustion, and all performance indicators were considered under the energy self-sufficient conditions. The ratio of biomass fed to the gasifier and the combustor was found to be 0.38:0.62 where the C, H and O atom efficiencies of the process achieved were 35.83, 53.19 and 40.31%, respectively. When employing heat exchanger network, the atom efficiency of the process could be improved (C: 42.49, H: 61.83, O: 45.21), while the ratio of biomass fed to the gasifier and the combustor increased to 0.46:0.54. The energy consumptions were reported by mass allocation as 143 MJ/kg-DMC. Since all energy was supplied by biomass itself, the process was considered as carbon neutral with a fraction of carbon dioxide fixation from biomass into chemicals of 0.31.
Created from Fastlane, Scopus look-up
Keywords: Biomass gasification; Dimethyl carbonate; Ethylene glycol; Process design; Process simulation

Prosumer solar power and energy storage forecasting in countries with limited data: The case of Thailand - Tongsopit, Sopitsuda; Junlakarn, Siripha; Chaianong, Aksornchan; Overland, Indra; Vakulchuk, Roman (Heliyon, 2024)
Forecasts of distributed energy resource deployment are becoming increasingly important in electric power purchase plans and difficult for countries with limited data. This study utilizes the Customer Adoption Model to forecast the deployment of behind-the-meter distributed solar photovoltaics and battery energy storage systems until the year 2050 and Thailand is used as a case study of the countries with limited data. Comparing methods and results from this study with those used in past studies shows that methodological choices can produce diverging results that shape investment plans and the estimated cost of power supplies. Several input variables of the Customer Adoption Model are discussed that will require continuous refinements as more data become available. The results show that pairing solar systems with batteries could in principle accelerate solar deployment and carbon emissions reduction but the high cost of batteries lengthens the payback period, raising questions about forecasting methodologies that rely mainly on the payback period. The methodological contribution points to a “chicken-and-egg” problem between forecasting and policy uncertainties: accurate forecasting depends on policy certainty, but getting policy right depends on accurate forecasting. Integrated scenario construction and the determination of a specific timeframe for achieving the adoption goal can help policymakers understand the impacts of different policy designs on distributed energy resource deployment and overcome this problem.
Created from Fastlane, Scopus look-up
Keywords: Energy storage; Forecasting; Prosumer; Solar PV; Tariff restructure; Thailand

Seven Women Entrepreneurs of Solar Energy - Chaianong, Aksornchan (2019)

Status Report on Gender Equality in Energy Sector - Baruah, Bipasha; Chaianong, Aksornchan (2019)

The economics of solar PV self-consumption in Thailand - Tongsopit, Sopitsuda; Junlakarn, Siripha; Wibulpolprasert, Wichsinee; Chaianong, Aksornchan; Kokchang, Phimsupha; Hoang, Nghia Vu (Renewable Energy, 2019)
Declining prices of solar photovoltaic modules and consumers’ interest in green electricity production are driving the prevalence of electricity “prosumers” worldwide. Prosumers are electricity consumers who produce electricity for their own consumption, using distributed energy technologies including distributed solar photovoltaics (DPVs). Many jurisdictions around the world are adjusting to this changing energy landscape by reforming their policies to support self-production and self-consumption of electricity. This paper analyzes the economics of electricity self-consumption of DPV electricity in Thailand. Based on our study, we assess the feasibility of DPV self-consumption schemes for four customer groups. Among the three schemes assessed, (no compensation for excess electricity, net metering, and net billing), all customer classes are profitable and net metering offers the most customer benefits. However, we recommend net billing for policy adoption, not only because of its sufficient level of economic viability but also its flexibility in addressing broad stakeholders’ concerns. Our analytical approach captures in detail how DPV sizing relative to the load may be impacted by those compensation mechanisms. Our methodology can be replicated by countries that would like to develop or reform their national-level DPV self-consumption policies during an energy transition.
Created from Fastlane, Scopus look-up
Keywords: Distributed solar PV; Net billing; Net metering; Rooftop PV self-consumption; Solar economics; Thailand solar PV policy

The Implications of Household PV-Battery Systems for Utilities in Thailand - Chaianong, Aksornchan; Bangviwat, Athikom; Menke, Christoph (Journal of Clean Energy Technologies, 2019)
Driven by decreasing PV and battery installation costs and mismatch between household demand and PV generation, household PV-battery systems are going to be deployed in the country and create significant implications for utilities in Thailand. This paper mainly discusses both negative and positive impacts of household PV-battery systems on Thai utilities. The use of household batteries (storing excess generation from PV during daytime and discharging it in the evening) can increase solar capacity values and energy values to power system, mitigate the problem of “duck curve” and decrease PV integration cost. Household customers can consume more PV electricity (increasing PV self-consumption ratio) from the inclusion of batteries. As a result, it leads to higher revenue losses and lower re-sale of exported electricity from PV to distribution utilities, while it is not the case for generation/transmission utilities since re-sale of exported electricity is only relevant to distribution power system and revenue losses of generation/transmission utilities remain unchanged. This is because with household batteries, the level of PV installation is the same (only shifting the consumption of household PV excess generation from daytime to evening). Therefore, it is necessary to precisely quantify each cost and benefit component in order to understand values of household batteries to the power syste
Keywords: Rooftop PV; battery; household; utility; Thailand.

Towards a collective vision of Thai energy transition: National long-term scenarios and socioeconomic implications - Junlakarn, Siripha; Pujantoro, Mentari; Chaianong, Aksornchan; Kokchang, Phimsupha; Prommuak, Chattip; Chuenwong, Kannaphat; Saelim, Supawan; Kumar, Samarth; De Vivero, Gustavo; Schiefer, Tessa (2022)

Unlocking rooftop solar PV in Thailand: Facilitating policy and financial de-risking instruments - Junlakarn, Siripha; Teerakiat, Peetiphat; Kokchang, Phimsupha; Chaianong, Aksornchan; Saelim, Supawan; Lütkehermölle, Katharina (2024)